1996
DOI: 10.1071/ar9961275
|View full text |Cite
|
Sign up to set email alerts
|

The genetic foundation of fitness and reproduction traits in Australian pig populations. 2. Relationships between weaning to conception interval, farrowing interval, stayability, and other common reproduction and production traits.

Abstract: Data sets from 2 large Australian piggeries were used to estimate genetic parameters for the traits weaning to conception interval (WCIi-l,i) and farrowing interval (FIi-l,i), number born alive (NBAI), average piglet birthweight (BWi), 21-day litter weight (W21i), and sow stayability (STAYli) recorded for each ith parity, as well as sow average daily gain (ADG) and backfat (BF) recorded at the end of performance test. Over parities and herds, heritabilities for each trait were in the ranges: WCI/FI, 0.0-0.10; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
52
2
8

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 36 publications
15
52
2
8
Order By: Relevance
“…Generally, results from this study were consistent with those reviewed by others (e.g. Rothschild and Bidanel, 1998) or estimated previously using data from this population (Tholen et al, 1996;Bunter et al, 2008). The relatively low genetic correlation between TB and APBW has also been observed previously in this particular population .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Generally, results from this study were consistent with those reviewed by others (e.g. Rothschild and Bidanel, 1998) or estimated previously using data from this population (Tholen et al, 1996;Bunter et al, 2008). The relatively low genetic correlation between TB and APBW has also been observed previously in this particular population .…”
Section: Discussionsupporting
confidence: 93%
“…With respect to FAR12, productive sows with good litter size and litter weight gains were more likely to survive to the next parity, as also seen previously in studies conducted by Tholen et al, (1996) and Serenius and Stalder (2006). Further, LITG and beneficial outcomes for sow body condition at weaning are favourably correlated with lactation intake overall.…”
Section: Discussionsupporting
confidence: 74%
“…In this study, there was some support for such a relationship, but the estimates were imprecise (r g LW-WSI7 = 0.43, PSD = 0.23; r g LW-WSI50 = 0.33, PSD = 0.21). Tholen et al (1996) estimated the genetic correlation between litter weight at 21 days and weaning-toconception interval for 1st-parity sows to −0.09. Bergsma et al (2008) found an unfavourable but not significant genetic correlation (0.15) and a phenotypic correlation close to zero between litter weight gain and prolonged interval.…”
Section: Correlationsmentioning
confidence: 99%
“…Considering that pre-farrowing body composition is thought to be an important factor for both sow longevity (Tholen et al, 1996b) and piglet mortality (Grandinson et al, 2005), and sow condition before mating can have a significant effect on condition before parturition (Guillemet et al, 2006), it is important that these associations are explored.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a similar pre-mating phenotype may be arrived at in very different ways, and presumably this has implications for future gilt performance. This potentially explains the relatively poor predictive capacity of absolute finisher and post-finisher performance traits for sow longevity (Tholen et al, 1996b;Serenius and Stalder, 2004) or indeed lactation feed intake (Bunter et al, 2007b) at the phenotypic level, as there are substantial changes to individual sow phenotypes in the intervening period.…”
Section: Discussionmentioning
confidence: 99%